The Role of Entrepreneurship in the Sustainable Development of Rural Areas in Russia - Polbitsyn, Sergey N. (Economy of Regions, 2021)
Analysis of numerous works on the historical development of agri-food production and the organisation of agri-food systems convincingly demonstrates that each development stage was organised to successfully meet the challenges of civilisation. Based on the analysis results, I hypothesise that there have been five historical stages of development of agri-food systems. Nowadays, both national and regional agri-food systems are increasingly introducing the institutions of the innovative agri-food system 6.0. The agri-food system 6.0 is based on a new perception of food security focused on identifying and satisfying the individual needs rather than meeting the basic food demand of the population. Numerous researchers have repeatedly noted that only entrepreneurs can consider specific and varying needs of different population groups, as, unlike large agricultural businesses, they have the flexibility to organise production and offer consumers the demanded products. An analysis of works on the historical development of agri-food systems in different countries, as well as a detailed study of agri-food production trends of the Russian agri-food system confirm the hypothesis. The research results determine the role of rural entrepreneurial ecosystems in the development of both the national agri-food system and rural areas. The obtained findings can help examine the role of individual actors in ensuring the sustainable development of the rural entrepreneurial ecosystem, as well as identify universal and specific factors influencing its development.